Social group and mobbing - Baltezarević Vesna (Temida, 2009)
Our reality, having been subject to the numerous social crises during the last decades of the 20th century, is characterized by frequent incidences of powerlessness and alienation. The man is more frequently a subject to loneliness and overcomes the feeling of worthlessness, no matter whether he considers himself an individual or a part of a whole larger social. Such an environment leads to development of aggression in all fields of ones life. This paper has as an objective the pointing out of the mental harassment that is manifested in the working environment. There is a prevalence of mobbing cases, as a mode of pathological communication. The result of this is that a person, subjected to this kind of abuse, is soon faced with social isolation. This research also aspires to initiate the need for social groups self-organization of which victims are part of. The reaction modality of a social group directly conditions the outcome of the deliberate social drama, one is subjected to it as a result of mobbing.